Rasgos de personalidad y autoestima en víctimas de acoso laboral (2010)
The current research aims at describing behaviors dealing with the job psychological relentless persecution as well as features of personality and self-esteem in people who have been victims and have been able to accuse this complex issue in front of legal instances. The participants were four women aged between forty-five and fifty-seven years old, with time of entailment over fifteen years, at public organizations. The research instruments applied were the Lipt-60 questionnaire, the BFQ test, the Rosenberg self-esteem scale and a semi-structured interview, too. The outcomes clearly reflect the presence of descending-vertical job psychological relentless persecution; each case is different from the other since they do not show similarities in the harassing actions and are also different regarding the intensity and the frequency of the strategies used by the pursuer towards the victim. Finally, in regard to the personality features, all cases present low fluctuations of affability and emotional stability.